Developing Artistic Competencies through Still Life in Visual Arts Education - Tolibova Umida Davlat qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
ANNOTATION: This article examines the role of still life painting in developing students’ artistic competencies in visual arts education. It focuses on pedagogical approaches for teaching compositional skills, color and shape perception, and aesthetic reasoning. The study highlights methods to foster students’ creativity, observational skills, and independent artistic thinking, drawing upon Shovdirov S.A.’s research in art pedagogy.